USING ENGLISH SONGS IN IMPROVING LISTENING SKILL AT EIGHTH GRADE STUDENTS IN MTS NEGERI 1 MANADO - Nikmala Nemin Kaharuddin; Srifani Simbuka; Andi Mukarammah Nagauleng; Regita Cahyani Ginoga (Universitas Muhammadiyah Gorontalo, 2021)
Abstract The purpose of this study was to determine the improvement in listening skill of students by using English songs in class VIII Students at MTs Negeri 1 Manado. This research used the classroom action research (CAR). The subject of this study were 29 students consisting of 16 female students and 13 male students. The data was collected by using test and observation. The data obtained in the cycle I indicated average score of 68.62 with the percentage of students who passed the test was 24.13% while in the cycle II, the average score was 80.84 with the percentage of students who passed the test was 93.10%. Meanwhile, based on observation in cycle I, the students listening skill were considered as deficient and some students could not listen properly to the songs that were played to them. On the other hand, in the cycle II students showed that they had been able to improve their listening skill through the use of English songs. The result showed that there was an improvement their listening skill through the use of English songs. Key words : Listening skill, songs